2021
DOI: 10.11604/pamj.2021.39.264.22909
|View full text |Cite
|
Sign up to set email alerts
|

Late antenatal care initiation and its contributors among pregnant women at selected public health institutions in Southwest Ethiopia

Abstract: Introduction early commencement of antenatal care by pregnant women as well as regular visits has the potential to affect maternal and fetal outcomes positively. Even with antenatal care, the intervention requires fewer resources; however, most pregnant women in sub-Saharan Africa have begun late for antenatal care services. This study aimed to assess the magnitude and contributors of late antenatal care initiation among pregnant women at selected public health institutions of the Bench-Sheko Zone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 24 publications
(53 reference statements)
0
6
0
Order By: Relevance
“…Women from rural areas were shown to have a reduced number of ANC visits compared with urban residents. This finding is supported by different studies conducted in Ethiopia [27,37,41], Guinea [45], Pakistan [46], the Philippines, and Indonesia [47]. This may be because women from rural areas have low access to health facilities and inadequate information on the importance of having an adequate number of ANC visits.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…Women from rural areas were shown to have a reduced number of ANC visits compared with urban residents. This finding is supported by different studies conducted in Ethiopia [27,37,41], Guinea [45], Pakistan [46], the Philippines, and Indonesia [47]. This may be because women from rural areas have low access to health facilities and inadequate information on the importance of having an adequate number of ANC visits.…”
Section: Discussionmentioning
confidence: 66%
“…Different studies were conducted in Ethiopia, but the previous studies were conducted on utilization level [22,23], time of initiation [3,[24][25][26][27], and associated factors [3,12,26] rather than focusing on the number of visits, which may result in loss of information in classification count data. Further, the previous studies were conducted with the older recommendation of WHO, which emphasis on focused four ANC visits.…”
Section: Introductionmentioning
confidence: 99%
“…Single interventions such as packaged health message improves ANC coverage and deliveries in health facilities 16 . Health information combined with the introduction and promotion of birth plans during ANC increased its utilization 17 . This has had a direct positive effect on health service utilization and increasing democratization of reproductive health decisions 18 .…”
Section: Discussionmentioning
confidence: 99%
“…The result from the 2016 Ethiopian DHS (EDHS) revealed only 20% of pregnant women in Ethiopia start their ANC during the first trimester of their pregnancy 12. Other studies in the country reported varying magnitudes of early initiation of ANC; the proportion was found to be 46.8% in Bahir Dar,13 21.71% in Southern Ethiopia,14 40.6% in Debre Markos,15 39.5% in Tselemt District of Tigray Region,16 27.5% in Axum,17 28.8% in Ilu-Ababor18 and 34% in Bench-Sheko Zone 19…”
Section: Introductionmentioning
confidence: 98%
“… 12 Other studies in the country reported varying magnitudes of early initiation of ANC; the proportion was found to be 46.8% in Bahir Dar, 13 21.71% in Southern Ethiopia, 14 40.6% in Debre Markos, 15 39.5% in Tselemt District of Tigray Region, 16 27.5% in Axum, 17 28.8% in Ilu-Ababor 18 and 34% in Bench-Sheko Zone. 19 …”
Section: Introductionmentioning
confidence: 99%